PENGARUH PENGGUNAAN KRIKIL MANTUP SEBAGAI BAHAN PERKERASAN JALAN (AC-WC) - Sugeng Dwi Hartantyo; Beni Hermanto (U Karst, 2019)
This research aims to find out how the process of making hot asphalt mixtures (AC-WC) using grated mantup as a substitute for coarse aggression, and aims to find out how the influence of using grated mantras as hot asphalt mixture (AC-WC) This research method used is the exprimental trial and error method of Marshall testing methodology to analyze the properties of percent cavity in the mixture (VIM), percent cavity filled with asphalt (VFB), percent cavity between mineral aggregate (VMA), stability (Stability) , melt (Flow) and Marshall Quatient. The substitution of cricile variation is 0%, 25%, 50%, 100% of the coarse aggregate weight in this study indicating that the most ideal Marshall Properties value is calculated using the regression model equation with the highest index of determination where the index value of determination is obtained ( R2) = 1 for Marshall properties which is the highest is the substitution of gravel mantup 100% with Marshall parameters which includes: Stability 979.03 kg, VIM 97.71%, VMA 18.68%, VFWA 78.21%, Flow 3.13 mm , Marshall Question 316.46%. From these results the substitution of Krikil Mantup with a level of 100% meets the criteria in Indonesian national standards.Keywords: Mantup Gravel, Manufacture, Hot Asphalt (AC-WC)Penelitian ini bertujuan untuk mengetahui bagaimana proses pembuatan campuran aspal panas (AC-WC) dengan menggunakan parutan mantup sebagai pengganti agresi kasar, dan bertujuan untuk mengetahui bagaimana pengaruh penggunaan parutan sebagai campuran aspal panas (AC-WC) . Metode penelitian yang digunakan adalah metode exprimental trial and error metodologi pengujian Marshall untuk menganalisis sifat persen rongga dalam campuran (VIM), persen rongga diisi dengan aspal (VFB), persen rongga antara agregat mineral (VMA), stabilitas (Stabilitas) ), melt (Flow) dan Marshall Quatient. Substitusi variasi cricile adalah 0%, 25%, 50%, 100% dari berat agregat kasar dalam penelitian ini menunjukkan bahwa nilai Marshall Properties paling ideal dihitung menggunakan persamaan model regresi dengan indeks penentuan tertinggi di mana nilai indeks penentuan diperoleh (R2) = 1 untuk sifat Marshall yang tertinggi adalah substitusi dari kerikil mantup 100% dengan parameter Marshall yang meliputi: Stabilitas 979,03 kg, VIM 97,71%, VMA 18,68%, VFWA 78,21%, Aliran 3,13 mm, Marshall Pertanyaan 316,46%. Dari hasil ini substitusi kerikil Mantup dengan tingkat 100% memenuhi kriteria dalam standar nasional Indonesia. Kata Kunci: Gravel Mantup, Pembuatan, Hot Asphalt (AC-WC)